Preventing proximal junctional failure in long segmental instrumented cases of adult degenerative scoliosis using a multilevel stabilization screw technique - Sandquist, Lee (Surg Neurol Int, 2015)
BACKGROUND: The authors sought to demonstrate the safety and effectiveness of the multilevel stabilization screw (MLSS) technique in decreasing the incidence of proximal junctional failure in long segmental instrumented fusions for adult degenerative scoliosis. METHODS: Institutional review board approval was obtained and all patients with adult spinal deformity who underwent the MLSS technique were analyzed. A neuro-radiologist and spine-focused neurosurgeon not involved with the surgical treatment performed radiographic analysis. Proximal junctional angle was defined as the caudal endplate of the upper instrumented vertebra (UIV) to the cephalad endplate of two supradjacent vertebrae above the UIV. The UIV is defined as the most cephalad vertebra completed captured by the instrumentation. Abnormal proximal junctional kyphosis (PJK) was defined as proximal junctional sagittal Cobb angle >10 degrees and proximal junction sagittal Cobb angle at least 10 degrees greater than the preoperative measurement. The presence of both is criteria necessary to be considered abnormal. RESULTS: Twenty patients with degenerative scoliosis underwent the MLSS technique with the upper-instrumented vertebrae in the proximal thoracic spine. Fifteen patients met inclusion criteria with greater than 12 months radiographic and clinical follow up. Three patients were excluded due to lack of follow up imaging and two patients were excluded due to the inability to measure the UIV. Age range was 44–84 years with a mean of 66. Eleven of the 15 patients were over the age of 60 at the time of surgery. The male-to-female ratio was 4:11. Body mass index (BMI) range was 24–44 with a mean of 31.5 units. The follow up period ranged from 14 to 58 months with an average follow up of 30 months. The mean change in Cobb angle at the proximal junction was 4.00 degrees with a range from -0.92 to 9.13 degrees. There were no fractures or instrumentation failures at or near the proximal junction. There was no revision surgeries performed for proximal junctional failure. Retrospective clinical questionnaires revealed that surgical expectations were met in 15 of 19 patients surveyed, 79%. One patient was not reachable for a postoperative phone interview. In patients who were not satisfied with their overall experience, the change in Cobb angle ranged from -0.92 to 9.13 degrees with an average change of 3.90 degrees. Whereas patients reporting an overall positive experience had a change in Cobb angle range from -0.12 to 8.07 degrees with an average change of 4.05 degrees. CONCLUSION: PJK and failure are well-recognized suboptimal outcomes of long-segmental fusions of the thoracolumbar spine that can lead to significant neurological morbidity and costly revision surgeries. With no known proximal junction failures to date, the MLSS technique has shown promising results in preventing adverse proximal junctional conditions and can be safely performed under fluoroscopy guidance. Future direction includes a comparative study establishing the relative risk of developing PJK with this novel technique versus a traditional long-segmental thoracolumbar fusion.